Avoidance Traffic Congestion Through Smart Transportation Approach - Chenguang Wang (Big Data and Computing Visions)
Recent times the concept of smart city gained so much of popularity because of internet of things technology. Smart parking is one of the ideas of smart city. Smart parking system used to monitor the status of every parking available. As society fosters the streets become more swarmed and vehicles fill in number there are different sort of circumstances on streets in view of atmospheric conditions and gridlocks because of mishaps or vehicles breakdowns and because of every one of these arriving at objective causes to feel like drained and aggravated. Also here comes the shrewd traffic framework IDs.